2016
DOI: 10.1007/s11657-016-0259-2
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral non-traumatic hip fractures in a heavy smoker COPD patient on inhaled steroids

Abstract: History of COPD with corticosteroid use may be used as a diagnostic tool to identify patients having osteoporosis. Preventive measures can be performed by monitoring high-risk patients with bone mineral densitometry, WHO fracture risk assessment tool (FRAX tool), serum calcium, and vitamin D levels to prevent bone fractures. Treating those patients with the lowest effective dose of corticosteroids should be targeted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Bilateral femoral neck fracture is extremely rare, and has been reported after a simple fall or by high-energy related trauma 5,6. However, hypocalcemia-induced seizure,7 hypophosphatasia-induced seizure,8 eclamptic seizure,9 chronic renal failure,10,11 heavy smoking,12 and narcotic drug abuse13 related femoral neck fractures are also reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bilateral femoral neck fracture is extremely rare, and has been reported after a simple fall or by high-energy related trauma 5,6. However, hypocalcemia-induced seizure,7 hypophosphatasia-induced seizure,8 eclamptic seizure,9 chronic renal failure,10,11 heavy smoking,12 and narcotic drug abuse13 related femoral neck fractures are also reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The published articles on such cases do not offer detailed information relating to which surgical approach was performed and how many stages were required for that matter. [10][11][12]17 One-stage arthroplasty was usually undertaken with posterolateral 13 or direct lateral approach. 5 Shah et al 4 reported bilateral femoral neck fracture following a generalized seizure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip fractures involving no or minimal trauma are uncommon and usually involve an underlying pathology. Causes identified in the literature include epilepsy,10 osteoporosis11 and metabolic bone disease such as osteomalacia,12–14 hyperparathyroidism15 16 and renal osteodystrophy 17…”
Section: Discussionmentioning
confidence: 99%
“…Significant associated factors are nicotine, reduced mobility and the loss of muscle mass, respiratory acidosis and systemic inflammation with a negative influence of interleukins and pre-existing osteopenia. Also, administration of glucocorticoids, negatively affects the skeleton (Sanel et al 2016). Key factor in accelerating bone loss in COPD is vitamin D deficiency.…”
Section: Chronic Obstructive Pulmonary Disease (Copd) and Bone Healthmentioning
confidence: 99%